Державне управління якістю вищої освіти в контексті норм міжнародних стандартів якості: принцип залучення персоналу - Мороз, Світлана Анатоліївна (Національний технічний університет "Харківський політехнічний інститут", 2017)
Розглянуто категорію якості вищої освіти в контексті норм міжнародного стандарту якості серії ДСТУ ISO 9000:2007, а саме змісту принципу залучення працівників; за результатами аналізу змісту паспортів спеціальностей педагогічних наук було визначено ті з напрямів в організації наукових пошуків, які можуть корелюватися з відповідними напрямами державно-управлінської науки; визначено потенціали використання принципу залучення працівників на університетському рівні, з’ясовано місце та роль студентів та науково-педагогічних працівників, а також суб’єктів державного управління у забезпеченні умов реалізації відповідного принципу; опрацьовано висновки щодо можливих напрямів удосконалення механізмів державного управління забезпеченням якості вищої освіти.

There were considered the category of higher education quality in the context of the norms of the international standard of quality of the series DSTU ISO 9000: 2007, namely the content of the principle of attraction of personnel; According to the results of the analysis of the contents of the passports of specialties of pedagogical sciences, it was determined those areas in the organization of scientific researches that may correlate with the corresponding directions of state-management science; the potential of using the principle of attraction of personnel at the university level is determined, as well as the place and role of students and scientific and pedagogical staff as well as subjects of state administration in ensign the conditions for the implementation of the corresponding principle; made conclusions regarding possible directions of improvement of the mechanisms of state administration in providing quality of higher education.
State management of the quality of higher education in the context of norms of international quality standarts: attracting of personnel
Keywords: принципи управління якістю; принцип залучення працівників; моніторинг якості освіти; міжнародний стандарт якості; higher education quality; principle of attracting staff